Tobramycin Blood Levels after Local Antibiotic Treatment of Bone and Soft Tissue Infection - Carlos D. Pargas; Ahmed H. Elhessy; Mehdi Abouei; Martin G. Gesheff; Janet D. Conway (MDPI AG, 2022)
Local antibiotic delivery using different carriers plays an important role in both infection prophylaxis and treatment. Besides dead space management, these carriers have the advantage of providing a high concentration of local antibiotics with a lower risk of systemic toxicity. Few studies have reported on systemic toxicity associated with antibiotic-impregnated carriers. The present study investigates the systemic tobramycin concentration at 24, 48 and 72 h postoperatively after using tobramycin-loaded polymethyl methacrylate (PMMA) and calcium sulfate (CS) as local antibiotic carriers. Additionally, this work assesses the renal function postoperatively for indications of acute kidney injury (AKI). Fifty-two patients were treated in 58 procedures with tobramycin and vancomycin-loaded PMMA, CS, or both. All systemic tobramycin levels were <2 mcg/mL at 72 h, and the resulting rate of AKI was 12% (7/58). In conclusion, local tobramycin antibiotic delivery using PMMA, CS, or both remains a safe and effective modality in the treatment of osteomyelitis as long as the surgeon is aware of its possible nephrotoxic effect.